Legal Review of Online Buying and Selling Transactions - Irwan Irwan; Muhammad Arief Saleh (Fox Justi : Jurnal Ilmu Hukum, 2026)
In online buying and selling practices, common issues include non-delivery of goods, items not as described, late delivery, and damaged goods, which can lead to legal issues. Losses can be experienced not only by consumers but also by businesses selling their goods using the cash on delivery payment method. Agreements made in online buying and selling transactions are still premature because buyers only see the goods listed in the advertisement. The purpose of this research is to determine the legal impact on online buying and selling transactions. The type of research used is normative and empirical research. The normative research is conducted through literature studies from various sources, including legislation, books, journals, and information from online media. Meanwhile, empirical research obtains field data as the main data source, such as the results of interviews and observations. Online buying and selling has the potential to lead to unlawful acts, especially criminal violations, such as providing false information about advertised products, deception between sellers and buyers because the goods that have been paid for do not reach the buyer, or vice versa, goods that have been purchased but not paid for by the buyer. Article 1321 of the Civil Code stipulates that an agreement is legally void if it is made through error, obtained through coercion, or fraud. Researchers recognize that the use of online media for electronic buying and selling transactions must be conducted wisely and in good faith, as potential negligence and crime can result in legal violations.